Sistematic Literature Review: Inovasi Media Pembelajaran Matematika yang Menarik dan Interaktif untuk Siswa - Fungky Marian (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
With the rapid advancement of the digital era, innovation in interactive and engaging mathematics learning media has become essential to enhance student engagement and comprehension. Interactive technologies such as mobile-based applications and educational game platforms offer significant potential to improve learning effectiveness. However, their implementation continues to face challenges, including limited teacher digital competence, inadequate infrastructure, and insufficient evaluation of media effectiveness. This study aims to identify innovative mathematics learning media that effectively enhance student motivation and learning outcomes, and to formulate strategies for overcoming implementation barriers. Using the Systematic Literature Review (SLR) method, the research analyzes 500 scientific articles from the Scopus database. Data were processed with VOSviewer to map research trends, co-occurrence of keywords, and thematic clusters. Findings reveal a significant surge in publications on innovative mathematics learning media in 2022, largely driven by the post-pandemic demand for technology-enhanced learning. Computer-based interactive multimedia has been shown to improve conceptual understanding, while social media platforms particularly TikTok are increasingly adopted as informal yet effective educational tools. Practically, these findings encourage schools and policymakers to strengthen teacher training in digital pedagogy, expand access to digital infrastructure, and strategically integrate interactive platforms including social media and AI-driven tools into everyday mathematics instruction